Collected measures of farmer preferences over risk and ambiguity using direct elicitation and behavioral games in a large sample - CGIAR Research Program on Policies, Institutions, and Markets (2017)
We collected endline data on risk and ambiguity aversion for the sample that comprised the census for the study. This is a sample of over 13,000 households and is the largest every collection of such data, which will be used to analyze how risk and ambiguity preferences affect technology adoption.